(untitled) (Metallurgy and Foundry Engineering, 2006)
This study presents some aspects of modeling of the mechanical behavior and strengthening mechanisms of HSLA and Ti-IF steels deformed under high strain rate conditions. Axisymmetrical compression tests at a wide range of strain rates have been performed to determine the mechanical and microstructural response of the material. The experimental data were compared with the results of computer modeling where proposed constitutive models are implemented in FEM code. The test data are used to find suitable values related to Zerilli-Armstrong model for microalloyed steels.